TRANSNATIONAL BUREAUCRATIC POLITICS: AN INSTITUTIONAL RIVALRY PERSPECTIVE ON EU NETWORK GOVERNANCE. (7th March 2016) - BACH, TOBIAS; DE FRANCESCO, FABRIZIO; MAGGETTI, MARTINO; RUFFING, EVA
Abstract : This contribution introduces our symposium by highlighting four distinctive aspects of transnational governance from a bureaucratic politics perspective: the emergence of transnational institutions, their functioning, their impact on the domestic level, and the diffusion of regulatory standards. The general argument is that many accounts of transnational governance seem to be overly optimistic about the conditions for effective problem‐solving and fail to take into account that institutional rivalry may either support or constrain the implementation of supranational policies. The aim of this piece is to review existing research, to highlight the contribution of the symposium articles in furthering an institutional rivalry perspective on transnational governance, and to sketch pertinent areas for further research building upon this perspective.